Aspekte gemeinsamer Agrarpolitik 2000 - Dirk Manegold (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– Agricultural Markets at the Turn of 2000/2001 (1) EU agricultural policy discussion focussed on two issues in 2000: EU enlargement and WTO negotiations. The approaching - yet unknown - date of Eastern enlargement is alerting EU farmers who fear growing competition to endanger their protected markets. Those fears are, however, countered by hinting to both, the impediments on the path of East European producers struggling for higher efficiency and the chances offering themselves to West European entrepreneurs on enlarged markets. Ongoing preparations for another round of agricultural trade negotiations give rise to highlight the weaknesses of the UR Agreement on Agriculture. Thereafter the positions of WTO member groupings are contrasted for better understanding the difficulties which the negotiations are likely to run into later this year.
Keywords: 330